Econometrics of first price auctions: A survey of the theoretical and applied literature - Gabrielli, Maria Florencia (2014)
The analysis of auctions is an active area of research for both theoretical and empirical economists. This paper provides an overview of the literature relevant to the econometrics of auctions from a structural approach perspective. The structural approach is a framework to analyze auction data in which theory and econometrics are closely related. There are three fundamental issues at the heart of the structural analysis: (i) Are there any testable restrictions imposed by the theoretic model on the data? (ii) Is it possible to identify the structural elements that characterize an auction without a priori parametric information? (iii) What can be said about feasible estimation procedures which do not rely on parametric assumptions?. This survey shows how the structural approach literature has answered each question.